The Information Component in the Structure of the Enterprise’s Economic Security - Borzenkova Olga D.; Shramko Olena O. (Bìznes Inform, 2017)
Developing the enterprise’s economic security consists in elaboration and implementation of a management system and a complex of activities aimed at the production and nonproduction spheres, with a view to ensuring an efficient economic performance, minimizing the factors of influence and threats in the changing external environment. The article defines the nature and role of the information component which consists of protection of the information environment, activities to prevent leakages of protected information, unauthorized and unintentional impacts on information, etc. The information security of enterprise is ensured by: legal measures at the level of the State and the level of enterprise; organizational support (i.e. regulation of the information flow at the enterprise); firmware (both software and hardware support to prevent illegal leakages of information).